From horizontal city to vertical city: rent of land as a perspective to understand changes in spatial forms in Vitória, Brazil - de Campos Junior, Carlos Teixeira (Geografares, 2024)
The focus of this research is Vitória (ES), which, in the 1940s, was still characterized as a horizontal city. However, the following decade saw an intensification of verticalization, initially concentrated in the central area and subsequently expanding into the coastal neighborhoods. During this time, land ownership was predominantly public, with transfers granted by the State upon payment of an annual fee. Government policies facilitated land occupation, including initiatives such as donating construction materials. A correlation can be observed between the transition from public to private land ownership and the methods of construction, which influenced the city’s spatial organization: Vitória transitioned from a horizontal layout to a vertical one as buildings were increasingly designed for rent or sale. The underlying hypothesis is that the privatization and instrumentalization of land, shaped by how space was constructed—whether for personal use, rental, or sale—provide key theoretical insights into understanding the city’s spatial transformation.
Keywords: rent of land; real estate production; space configuration; Vitória; Brazil